The General Procurators of the Teutonic Order Towards the Polish-Teutonic Conflict - Bar, Přemysl (Acta Poloniae Historica, 2023)
The article deals with the activities of the General Procurators of the Teutonic Order regarding the Polish-Teutonic dispute in the first thirty years of the fifteenth century. Based on their dispatches sent to Marienburg, it can be assumed that the Procurators were not passive executors of the Grand Master’s orders. Their frequently occurring disagreements resulted not only from their distinctive personal qualities but also from their different perspectives on assessing what was in the best interest of the Teutonic Order. The Grand Masters lacked professional knowledge not only of law (especially canon law) but also of how the Roman curia functioned.